Utilization of dairy waste scum oil for microwave-assisted biodiesel production over KOH-waste eggshell based calcium oxide catalyst - Mohd Johari, Siti Aminah; Ayoub, Muhammad; Lee, Jhung Zhi; Rashidi, Nor Adilla; Shamsuddin, M Rashid (Center of Biomass & Renewable Energy (CBIORE), 2024)
The sustainability can be maintained by utilizing the available waste as feedstock and catalyst such as dairy and eggshell waste respectively for biodiesel production. In this study, the calcium oxide (CaO) synthesized from calcined eggshell was doped with potassium hydroxide (KOH-ECaO) via wet impregnation method and analyzed the catalyst performance on biodiesel production from dairy waste scum oil (DWSO) via microwave assisted transesterification. The catalyst was characterized by X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy equipped with Energy Dispersive X-ray (SEM-EDX), Brunauer-Emmett-Teller (BET) and Thermogravimetric analysis (TGA). The fatty acid methyl ester (FAME) contents were deduced by Gas Chromatography-Mass Spectrometry (GC-MS). The KOH-ECaO catalyst showed a good potential based on the characterizations analysis such as high pore size (25.5 nm) which supported by SEM pattern analysis. The highest biodiesel production (75%) was obtained at optimum reaction parameters conditions. The optimized conditions were discovered to be 3 wt.% of catalyst, 16:1 of methanol to oil molar ratio, reaction temperature of 65°C and 15 minutes of reaction time as microwave provided faster reaction for the transesterification. These innovative results showed that KOH-ECaO could enhance the biodiesel production from DWSO which encouraged the usage of waste for wealth product.